Proceedings of the 2013 ACM Conference on Pervasive and Ubiquitous Computing Adjunct Publication 2013
DOI: 10.1145/2494091.2499574
|View full text |Cite
|
Sign up to set email alerts
|

Decentralised approach for a reusable crowdsourcing platform utilising standard web servers

Abstract: Crowdsourcing has gained increasing interest during the last years as means for solving complex tasks with the help of a flexible group of contributors. The crowd can contribute with collecting data in the field, completing map information or votes for ideas or products. Even though the participation of large numbers of users with heterogeneous devices in crowdsourcing is a highly recurrent task, generic infrastructures for crowdsourcing can be hardly found. Especially the management of users, mobile devices a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…They discussed reactive measures to robustly cleanse out abnormal data components from the original corrupted sensing data. Hara et al identified that heterogeneous devices come to be involved in crowdsourcing environments [27]. While finding generic infrastructures can be very difficult, they think having a generic reusable platform to support development of crowdsourcing applications would help in supporting heterogeneous mobile devices as well as manage large numbers of users.…”
Section: Crowdsourcing For Ubiquitous and Pervasive Computingmentioning
confidence: 99%
“…They discussed reactive measures to robustly cleanse out abnormal data components from the original corrupted sensing data. Hara et al identified that heterogeneous devices come to be involved in crowdsourcing environments [27]. While finding generic infrastructures can be very difficult, they think having a generic reusable platform to support development of crowdsourcing applications would help in supporting heterogeneous mobile devices as well as manage large numbers of users.…”
Section: Crowdsourcing For Ubiquitous and Pervasive Computingmentioning
confidence: 99%